Pengaruh Komposisi Tepung Komposit TESOTA (Terigu, Sorgum, Tapioka) dan Konsentrasi Karagenan Terhadap Mutu Roti Tawar Rendah Gluten - Aflah, Abid Jalaluddin; Widyastuti, Sri; Amaro, Moegiratul; Rasyda, Riezka Zuhriatika (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2024)
This study aimed to determine the effect of composite flour composition (wheat, sorghum, and tapioca) and carrageenan concentration on the quality of low-gluten white bread. This study used an experimental method with a two-factor completely randomized design (CRD), namely (1) composite flour composition (wheat:sorghum:tapioca) T1 = 50:25:25, T2 = 40:30:30, and T3 = 30:35:35, and (2) carrageenan concentration of 0.2 and 0.4%. Observation data were analyzed with SPSS software using ANOVA at the 5% significance level. Data that were significantly different were further tested with Honest Significant Difference test at the 5% significance level. The parameters observed included chemical quality (moisture content, ash content, and crude fiber content), physical quality (expandability, elasticity, bread pores, and staling), and organoleptic quality (aroma, taste, texture, crust color, and crumb color). The results showed that the treatment of different flour compositions and carrageenan concentrations had a significant effect on ash content, crude fiber content, expandability, elasticity, bread pores, and staling. However, there was no significant effect on its moisture content and organoleptic quality. To minimize the use of wheat flour, the composition of wheat:sorghum:tapioca flour 40:30:30 and carrageenan concentration 0.4% is the recommended treatment, with 24.35% moisture content (met the SNI requirements), 1.49% ash content, 4.08% crude fiber content, 68.69% expandability, 82.55% elasticity, pore size tends to be uniform between 12.08-19.11µm, staling time on the third day, and preferred by panelists because the texture is rather soft, the color of the crust is yellowish brown, and the color of the crumb is yellowish white.